Channeling effect in electronic spectra produced by grazing impact of fast protons on insulator surfaces - Archubi, Claudio Darío (2009)
Electron emission due to grazing scattering of fast protons from LiF and KCl surfaces is studied under axial incidence conditions. The differential emission probability is calculated within a distorted-wave formalism, taking into account axial channeled trajectories. For different emission angles, electronic spectra for proton incidence along the two principal crystal axes ([100] and [110]) are compared with those corresponding to an impact velocity in a random direction, finding effects associated with the channeling conditions.